2017
DOI: 10.1111/anu.12532
|View full text |Cite
|
Sign up to set email alerts
|

Dietary effects of soybean products on gut microbiota and immunity of aquatic animals: A review

Abstract: Soybean meal (SBM) is one of the most commonly used vegetable ingredient to replace fish meal in fish diets. However, SBM is limiting in some essential amino acids and contains numerous antinutritional factors and antigens that can affect intestinal microbiota and innate immune system in several finfish species and crustaceans and compromise health. The impact of SBM on health and gut microbiota of aquatic animals is not only affected by SBM in general, but also on the degree of treatment of the meal and expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
96
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(97 citation statements)
references
References 158 publications
0
96
1
Order By: Relevance
“…Typically the onset of SBM‐induced enteritis is accompanied by alterations of the microvilli and mucosal folds. These changes often induce a perceptible shift in the autochthonous bacteria community (Bai et al, ; Dawood et al, ; Merrifield et al, ; Zhou et al, ). In conclusion, it seems plausible that also the colonization process of the applied probiotic isolates is thereby comprehensively impeded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically the onset of SBM‐induced enteritis is accompanied by alterations of the microvilli and mucosal folds. These changes often induce a perceptible shift in the autochthonous bacteria community (Bai et al, ; Dawood et al, ; Merrifield et al, ; Zhou et al, ). In conclusion, it seems plausible that also the colonization process of the applied probiotic isolates is thereby comprehensively impeded.…”
Section: Discussionmentioning
confidence: 99%
“…However, the utilization of fishmeal is becoming increasingly restricted. Vast overfishing and a growing demand in animal nutrition led to an alarming scarcity and consequently a drastic increase in costs (Henry, Gasco, Piccolo, & Fountoulaki, 2015;Tacon & Metian, 2008;Zhou, Ringø, Olsen, & Seong, 2018). Thus, the exploration of new sources of feedstuff to promote a cost-efficient and a sustainable production of aquatic animals is the major challenge for the growing aquaculture industry (Henry et al, 2015;Olsen & Hasan, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In general, cytokines consist of pro‐inflammatory cytokines (e.g., IFN‐γ, IL‐1β, IL‐8, IL‐15 and IL‐17D) and anti‐inflammatory cytokines (e.g., TGF‐β, IL‐4, IL‐10 and IL‐11) in fish (Song et al, ; Zhou, Ringø, Olsen, & Song, ). A previous study found that taurine could down‐regulate IL‐1β and IL‐10 mRNA levels in the intestines of European sea bass (Rimoldi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, protein kinase C (PKC) could mediate influence of oxidative stress on epithelial mucus secretion, probably through triggering PI3K and MAPK pathways (El Homsi et al, 2007;Lee, Crawley, Hokari, Kwon, & Kim, 2010). The intestinal microbiota serves as a primary stimulus for shaping and modulating intestinal function (Ringø et al, 2016;Zhou, Ringø, Olsen, & Song, 2017). However, the antigenic nature of indigenous bacteria and the sensitive nature of host cells contribute to a precarious relation under stress conditions, which could alter intestinal function and disease susceptibility (Collins & Bercik, 2009).…”
mentioning
confidence: 99%